Trends and Trajectories on Brunei’s Political Discourse Studies: a Bibliometric Analysis (International Journal of Linguistics and Indigenous Culture, 2024)
This bibliometric study aims to illuminate the evolution of the study of political discourse in Brunei over the past decade by (i) identifying current trends in the publication of Brunei’s political discourse, and (ii) determining the dominant theme in scholarly focus within the study of Brunei’s political discourse. To achieve this, performance analysis and scientific mapping were performed using Publish or Perish (PoP) and VOSviewer. Data from Google Scholar were filtered, yielding 165 relevant articles. PoP facilitated performance analysis, while VOSviewer visualized keyword clusters to ensure systematic analyses. Findings from the performance analysis reveal scholars’ interdisciplinary approach, intertwining disciplines such as history, sociology, law, and linguistics in studying political discourse trends. Meanwhile, findings from science mapping provide a comprehensive exploration of thematic convergence through three clusters in the landscape of political discourse studies in Brunei. These clusters highlight dominant themes, such as ‘identity,’ ‘power,’ and ‘religion’ in cluster 1. This exploration significantly contributes to the body of knowledge about political discourse, serving as a valuable resource for scholars, policymakers, and researchers seeking to understand the complex nuances of studying Brunei’s political discourse. Overall, this study not only enhance readers’ understanding of the current state of political discourse research in Brunei but also provide a roadmap for future scholarly inquiry in this dynamic and evolving field.